LAURACEAE - A. J. G. H. KOSTERMANS (Reinwardtia, 1957)
An attempt has been made at a classification of the Lauraceae, into taxa down to the rank of subgenus. The characters and their taxonomic value are discussed amply. A system of the family and keys are given. Two subfamilies, viz Lauroideae and Cassythoideae, are recognized; several new tribes, subtribes and subgenera have been described. The accepted genera, 31 in number, are surveyed, with synonyms, typification, description, and particulars. Additional notes to "The genera of Lauraceae", which appeared in 1952, are given.